(3OhQ GdbGVi ai EYGOI GdJhGRf GdGbJUGOi GdeNJd ddYbO HSHH GdXQha GdWGQFI (B: s (3OQGSI ebGQfI (B/ s - (3fhQ GdOjf LGH Gddg YHOGdSdGes; (3SYjO SdjeGf LHQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3oJnYoqO fXQjI GdXQha GdWGQFI GSJKfGkA Ydi bGYOI (B"(3GdYbO TQjYI GdeJYGbOjf(B": (3h bO eQJ GdfXQjI HJWhmQ JGQjNmqj MJi hUdJ Edi eG hUdJ Edjg GdBf ef fXQjmI eJcGedI GdHfGA h YGeI GdJWHjb(B: (3Ydi GdQZe ef Cf gfGc GpqJLGkgG aj Gdabg hGdbVGA hGdbGfhf GdeOfj QGakVG (B- (3h HTOmI (B- (3GdCNnP HGdfXQjI(B: (3h bO SGb CfUGoQ GdfXQjI YOnI CSmS oJnHpqQoQ GdCNP HgG h oJnYpqQoV cnqd hGMmO efgG ddfbO(B. (3h jfHZj dJWHjb GdfXQjI JhGaoQ YOI TQhmW efgG eG jJYdb HGdYbhO GdJj jLhR JWHjbgG YdjgG(B: (3MjK cGf gfGc GNJdGla Mhd cmqd ef GdYbhO GdGMJeGdjI(B: (3GdeMOOI(B: (3GdRefjI h GdahQjI(B: (3h gfGc TQhlW CNQi JJYdb HGdXQa GdPi jDpqOj Edi JWHjbgG(B: (3ajfHZj Cf jchf GSJKfGFkqjG(B: (3YGkqeG(B: (3djS aj GdEecGf JhoqboYg Ch OaoYg(B: (3h CNjkQG Cf jLYd GdGdJRGe eQgkbG(B. (3h JbJQH fXQjI GdXQha GdWGQFI ef GdbhI GdbGgQI(B: (3GdZHf GddGMb(B: (3GdGSJZdGd h GdEPYGf(B: (3dOQLmI jUYH GdJejjoR HjfgG(B: (3EdG Cfg jHbi dJdc GdfXQjI NUGFoU PGJjlI h ebheGlJ NGUlI JLYdgG fXQjkI bGFekI HPGJgG h dgG YfGUQgG h edGeMgG GdbGfhfjI GdJj JejRgG Yf ZjQgG(B. (3ebJVi GdabQI GdKGfjI ef GdeGOI (B(147) (3eOfj (B((3eUQj(B: (3djHj(B) (3GdebUhO HfXQjI GdXQha GdWGQFI Ch GdMGOK GdWGQF(B: (3gh cd MGOK YGe(B: (3dGMb Ydi Jchjf GdYbO(B: (3h ZjQ eJhnqbY GdMUhd YfO GdJYGbO(B: (3jfLe Yfg GNJdGld nHpqjlf aj GdefGaY GdeJhnqdOI Yf YbmO jJQGNi JfajPg Edi nCnLmd Ch BLGd(B: (3hjUHM JfajP GdeOjf dGdJRGeg ceG ChLHg GdYbO jQgbg EQgGkbG TOjkOG(B: (3jJgOOg HNSGQmI aGOMmI JNQL Yf GdMpqO GdeCdha aj NSGFQ GdJLGQ(B: (3h Pdc cNQhL SdYmI nJnYnqgnO GdeOjf HJhQjOgG ef GdJSYjQI hGQJaGY SYQgG GQJaGkYG aGMkTG ZjQ eCdha h dG eJhnqbYs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2018s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B194-202s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdeOfjs; (3GdXQha GdWGQFIs; (3GdYbOs; (3GdbhIs; (3GdJhGRf GdGbJUGOis; (3GdeOI GdRefjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs